RESEARCH OF THE PROBLEMS AND PERSPECTIVES OF THE DEVELOPMENT OF RESTAURANT ENTERPRISES - Balandina, І.; Chmutova, V. (Municipal economy of cities. Series: «Economy science», 2022)
Analyzing the market and forming general trends, which is the main task for the development of the restaurant business, it is expedient to create conditions for Ukrainian entrepreneurs to develop and promote new business ideas, filling relevant niches and improving such a sought-after industry as the restaurant business.. The directions of development of enterprises in the restaurant industry and the field of tourism over the last ten years have been considered. Mechanisms of restaurant industry development are analyzed. The need to introduce an innovative approach to the restaurant business to increase competitiveness through the use of new formats of the restaurant business, which will make it possible to retain existing customers and attract new visitors, is characterized. The purpose of this study is to determine and consider the financial and economic situation of production establishments in the hotel and restaurant industry, to study the problems of the work of enterprises in the field of hospitality, and to offer an interpretation of their own directions for their solution, applying innovative methods at the present stage. In accordance with the set goal, the following tasks are solved, such as the introduction of a system of economic motivation, which will allow everyone to be involved in the process of restaurant business development and take into account the economic interest of stakeholders. Considering the management aspect of industry leaders, we can conclude that it is quite appropriate for business owners to cooperate with actors, politicians, showmen and other popular personalities, which significantly guarantees public attention to the restaurant and its PR. So, as a result of the conducted research, it was determined that the main task of economic motivation and development of the restaurant business is to ensure its compliance with the effective use and development of innovations. To solve this issue, it is necessary to use the system of economic motivation, which makes it possible to create objective conditions for coordinating the actions of all participants in the process, taking into account the system of economic goals and interests.